Clostridium butyricum MIYAIRI 588-Induced Protectin D1 Has an Anti-inflammatory Effect on Antibiotic-Induced Intestinal Disorder - Ariyoshi, Tadashi; Hagihara, Mao; Eguchi, Shuhei; Fukuda, Aiki; Iwasaki, Kenta; Oka, Kentaro; Takahashi, Motomichi; Yamagishi, Yuka; Mikamo, Hiroshige (Frontiers in Microbiology, 2020)
Metabolites are the end products of cellular regulatory processes and have a strong correlation to phenotype. In our previous study, the administration of Clostridium butyricum MIYAIRI 588 (CBM 588) upregulated protectin D1, is one of the anti-inflammatory lipid metabolites, in colon tissue under the antibiotic therapy. However, how CBM588 induces protectin D1 nor whether the metabolite has anti-inflammatory effects on antibiotic-induced inflammation is unclear. Therefore, we evaluated the impacts of CBM588 on lipid metabolism and protectin D1 on gut protection from antibiotic-induced intestinal disorder. In the CBM 588 treatment group, gene expression levels of lipid receptor, related to DHA metabolism to protectin D1, such as polyunsaturated fatty acids (PUFAs) receptors, G-protein coupled receptor 120 (GPR120) and 15- lipoxygenase (LOX), were increased in colon tissue. IL-4 producing CD4+ cells, is main component of Th2 cells and can activate 15-LOX, also increased in CBM 588 treated groups even under CLDM co-administration. In addition, similar to CBM 588, protectin D1 exogenous administration reduced inflammatory cytokines, while anti-inflammatory cytokine, such as IL-10 and TGF-β1, were increased. Our data revealed that CBM 588 activate 15-LOX to enhance protectin D1 production through IL-4 producing CD4+ cells upregulation in the intestinal tract. Additionally, it became clear that CBM 588 induced-protectin D1 upregulated IL-10 producing CD4+ cells to control antibiotic-induced gut inflammation. We provide as a new insight that lipid metabolism induction for the treatment of gut inflammatory diseases with CBM 588.